The effect of bilateral rectus sheath and oblique subcostal transversus abdominis plane blocks on mechanical power in patients undergoing laparoscopic cholecystectomy surgery: a randomized controlled trial - Esma Karaarslan; Yasin Tire; Mahmut Sami Tutar; Nuran Akıncı; Hasan Alp Mermer; Sami Uyar; Dilek Ateş; Gürcan Şimşek; Betül Kozanhan (BMC Anesthesiology)
Abstract Background In this study, we aimed to investigate the effects of bilateral rectus sheath blocks (RSBs) and oblique subcostal transversus abdominis plane (OSTAP) blocks on mechanical power (MP) in patients receiving laparoscopic cholecystectomy under general anesthesia. Additionally, we sought to evaluate the impact of these blocks on postoperative pain and quality of patient recovery. Methods In this prospective, double-blind study, 66 patients who underwent laparoscopic cholecystectomy were randomized into two groups: Group C (control), which received a standard analgesic intravenous regimen; and Group B (block), which received bilateral RSB and OSTAP blocks. Intraoperative mechanical power was measured for all patients. Postoperative pain was assessed using visual analog scale (VAS) scores, and recovery quality was measured using the 15-item quality of recovery (QoR-15) questionnaire. Results The mechanical power values for patients in Group C were consistently greater at all measured times: baseline, before bridion, and after bridion. Although the difference at baseline was not statistically significant, significant differences were observed before and after bridion (p values = 0.112, 0.021, and 0.003, respectively). Patients in Group B exhibited significantly lower VAS scores at all time points (30 min, 2 h, 8 h, and 24 h) (p < 0.05). Additionally, essential variations were noted in the administration of rescue analgesia between the groups (p < 0.001). Regarding tramadol consumption, Group C patients had significantly greater values [84 (74–156) vs. 0 (0–75), median (25–75th percentiles)] (p < 0.001). For the QoR-15 scores, Group C also had significantly greater values [129 (124–133) vs. 122 (115–125), median (25–75th percentiles)] (p < 0.001). Conclusions Bilateral RSB and OSTAP blocks significantly reduce mechanical power during surgery. Moreover, they significantly decrease postoperative pain and analgesic consumption and increase patient recovery scores. Trial registration The study protocol was registered in the international database ClinicalTrials.gov (registration no. NCT06202040). This study was conducted between December 2023 and January 2024 at the Department of Anesthesiology and Reanimation of Konya City Hospital.